Supercooled sodium acetate aqueous solution for long-term heat storage to support heating decarbonisation. (15th November 2022) - Lizana, Jesus; Sanchez-Jimenez, Pedro E.; Chacartegui, Ricardo; Becerra, Jose A.; Perez-Maqueda, Luis A.
Abstract: Heating decarbonisation through electrification requires the development of novel heat batteries. They should be suitable for the specific application and match the operation conditions of domestic renewable energy sources. Supercooled liquids, often considered a drawback of phase change materials, are among the most promising technologies supporting heating decarbonisation. Although some studies have shed light on stable supercooling, the fundamentals and stability remain open problems not always accompanied by relevant experimental investigations. This research critically analyses the physic and chemistry of sodium acetate (SA, NaCH 3 COO) aqueous solution, a low-cost, non-toxic, and abundant compound with stable supercooling for long-term heat storage. It has an appropriate phase change temperature for high-density heat storage using heat pumps or solar thermal technologies in residential applications. The existing discrepancies in literature are critically discussed through a systematic experimental evaluation, providing novel insights into efficient material design and appropriate boundary conditions for reliable material use in long-term heat batteries. Despite previous studies showing that the thermal reliability and stability of sodium acetate aqueous solution as a supercooled liquid for heat storage cannot be guaranteed, this study demonstrates that through an appropriate encapsulation and sealing method, the peritectic composition of sodium acetate solution (p-SA 58 wt%) can be used as a supercooled liquid for long-term heat storage with a stable melting temperature of 57 °C, appropriate for domestic heat technologies. It is demonstrated that energy storage efficiency can be maintained under cycling, with a constant latent heat storage capacity of 245 kJ/kg and a volumetric storage density of 314 MJ/m 3 . It was confirmed that the material should achieve a fully-melted state for stable supercooling. Finally, local cooling and retaining seed crystals through high pressure were highlighted as the most suitable basic principles for successful crystallization and heat release. This promising material can store energy for long periods without latent heat losses due to its stable subcooling. Latent heat can be released when required at any selected time and temperature just by a simple activation process. Highlights: Supercooled liquid with appropriate characteristics for heat storage in buildings. Existing discrepancies in literature are critically studied and discussed. Optimal material design through the encapsulated and sealed peritectic composition. Suitable for heating applications and matching the operation condition of heat pumps Heat can be stored and released when required at any selected time and temperature.